Dry dispersion method, pole piece preparation method, secondary battery including pole piece, battery module, battery pack and power-consuming device
Through step-by-step feeding and heating casting, the existing secondary battery manufacturing technology is solved, the problems of complex, high price and high risk are achieved, and the secondary battery pole with excellent adhesive force and internal resistance of the diaphragm are reduced. Cost and risk.
Patent Information
- Application Number
- CN202210048006.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-17
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-01-17
AI Technical Summary
The existing secondary battery manufacturing technology has problems such as complex process, high price and high risk, and it is difficult to balance market demand and price.
By adding step by step, the agglomeration between the adhesive and the conductive agent in the dry coating material is reduced, and the surface of the active material of the secondary battery is wrapped with a dense adhesive and conductive agent bonding layer by heating casting. .
The secondary battery pole plate with excellent adhesive strength and diaphragm internal resistance is achieved, reducing production costs and risks, and improving product uniformity and performance.
Smart Images

Figure CN115832226B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a dry dispersion method, a pole piece preparation method, a secondary battery, a battery module, a battery pack and an electrical device comprising the pole piece. Background Art
[0002] At present, facing the coming TWh era, the sales volume of secondary batteries is also increasing, and domestic leading enterprises are also constantly deploying production capacity. However, in the face of market incentive competition, the original secondary battery manufacturing technology is difficult to balance the market demand price, so major secondary battery manufacturers have begun to work on dry process technology development. Only low-price, low-risk products can survive better. However, the existing technology has the problems of complex process, high price and high risk. Therefore, improving secondary battery manufacturing technology is still an urgent problem to be solved. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the present application minimizes the agglomeration phenomenon between the adhesive and the conductive agent of the dry coating material by adding materials in steps, and wraps the surface of the secondary battery active material with a dense adhesive and conductive agent bonding layer by heating casting, so that a secondary battery electrode with excellent adhesion and membrane internal resistance is obtained through a dry coating process.
[0004] According to a first aspect of the present application, there is provided a method for dry dispersing a secondary battery active material, a binder and a conductive agent, the method comprising:
[0005] (1) blending the secondary battery active material and a first binder, and performing heat casting to form a first blend; and
[0006] (2) mixing the first blend and the first conductive agent, and performing heating and casting to form a second blend;
[0007] Wherein, based on the weight of the second admixture, the content of the secondary battery active material is 80-99% by weight, and the content of the first adhesive is 0.5-10% by weight; wherein, based on the weight of the final product, the content of the first conductive agent is 0.5-5% by weight. In this method, by adding the adhesive first and then the conductive agent in a step-by-step manner, the phenomenon of agglomeration between the adhesive and the conductive agent in the dry coating material can be greatly reduced. In addition, the heating and casting of each after adding the adhesive and the conductive agent can promote the adhesive and the conductive agent to densely wrap the surface of the secondary battery active material, providing excellent electrode adhesion and membrane internal resistance.
[0008] In an embodiment of the present application, the method further includes:
[0009] (3) blending the second blend and a second binder, and performing heat casting to form a third blend; and
[0010] (4) The third blend and the second conductive agent are blended and heated and cast to form a fourth blend, wherein the second binder content is 0.5-10 wt % and the second conductive agent content is 0.5-5 wt % based on the weight of the fourth blend.
[0011] In this method, the phenomenon of agglomeration between the adhesive and the conductive agent in the dry coating material can be minimized by multiple (repeated) step-by-step additions. In addition, the heating and casting of the adhesive and the conductive agent after multiple additions can better promote the adhesive and the conductive agent to densely wrap the surface of the secondary battery active material, providing better electrode adhesion and membrane internal resistance.
[0012] In an embodiment of the present application, the method further comprises: repeating steps (3) and (4) at least once. In the method, steps (3) and (4) can be repeated multiple times, but based on cost efficiency, it is preferred to repeat steps (3) and (4) once.
[0013] In an embodiment of the present application, the content of the secondary battery active material is 90-99% by weight, the content of the first adhesive is 1-4% by weight; and the content of the first conductive agent is 0.5-2% by weight. In this method, by making the content of the secondary battery active material, the first adhesive and the first conductive agent within the above content range, a pole piece membrane with reduced resistance, increased adhesion and better uniformity can be better prepared.
[0014] In an embodiment of the present application, the first adhesive and the second adhesive are the same or different, wherein the content of the second adhesive is 1-4 weight %; and
[0015] The first conductive agent and the second conductive agent are the same or different, and the content of the second conductive agent is 0.5-2% by weight. In this method, by making the contents of the secondary battery active material, the first adhesive, the second adhesive, the first conductive agent and the second conductive agent within the above content range, a pole piece membrane with reduced resistance, increased adhesion and better uniformity can be better prepared.
[0016] In the embodiment of the present application, the blending is performed in a high-speed mixer at a speed of 1500-2000 rpm; and the heating casting is performed in a high-speed mixer and a mold temperature unit at a heating temperature of 150-250°C. In this method, by blending and heating casting in a high-speed mixer and a mold temperature unit, not only can the agglomeration phenomenon between the adhesive and the conductive agent of the dry coating material be minimized, but also the surface of the secondary battery active material can be wrapped with a dense adhesive and conductive agent bonding layer, so that a secondary battery pole piece with excellent adhesion and membrane internal resistance is obtained through a dry coating process.
[0017] According to a second aspect of the present application, a method for preparing a secondary battery pole piece by dry coating is provided, the method comprising:
[0018] The second blend or the fourth blend prepared by the dry dispersion method is applied to the current collector by dry coating. Through this method for preparing a secondary battery pole piece, the present application can ensure that the pole piece has reduced resistance, increased adhesion and improved uniformity.
[0019] According to a third aspect of the present application, a secondary battery is provided, wherein the secondary battery comprises an electrode sheet prepared by the above method for preparing a secondary battery electrode sheet.
[0020] According to a fourth aspect of the present application, a battery module is provided, comprising the secondary battery described in the present application.
[0021] According to a fifth aspect of the present application, a battery pack is provided, comprising the secondary battery or battery module described in the present application.
[0022] According to the sixth aspect of the present application, an electrical device is provided, which includes the secondary battery, battery module or battery pack described in the present application, and the secondary battery or the battery module or the battery pack is used as a power source for the electrical device or an energy storage unit for the electrical device.
[0023] Compared with the prior art, the dry dispersion method of the present application can minimize the agglomeration phenomenon between the adhesive and the conductive agent of the dry coating material, and wrap the surface of the secondary battery active material with a dense adhesive and conductive agent bonding layer, thereby obtaining a secondary battery electrode with excellent adhesion and membrane internal resistance through a dry coating process.
[0024] These and other features and advantages will become apparent by reading the following detailed description and by reference to the associated drawings.It is to be understood that the foregoing general description and the following detailed description are illustrative only and are not restrictive of the aspects of what is claimed. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1It is a flow chart of the dry dispersion method in a specific embodiment of the present application.
[0026] Figure 2 This application Figure 1 Scanning electron microscope (SEM) images of each step of the flow chart shown.
[0027] Figure 3 It is a schematic diagram of a high-mix machine in a specific implementation manner of the present application.
[0028] Figure 4 It is a schematic diagram of one embodiment of the secondary battery of the present application.
[0029] Figure 5 yes Figure 4 An exploded view of a secondary battery is shown.
[0030] Figure 6 It is a schematic diagram of an embodiment of a battery module of the present application.
[0031] Figure 7 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0032] Figure 8 yes Figure 7 Exploded view of the battery pack shown.
[0033] Fig. 9 This is a schematic diagram of one embodiment of a device using the secondary battery of the present application as a power source.
[0034] Description of reference numerals:
[0035] 1. Battery Pack
[0036] 2. Upper box
[0037] 3. Lower box
[0038] 4. Battery module
[0039] 5. Secondary battery
[0040] 51. Shell
[0041] 52. Electrode assembly
[0042] 53. Cover DETAILED DESCRIPTION
[0043] The present application is described in detail below in conjunction with the accompanying drawings, and the features of the present application will be further revealed in the following specific description.
[0044] "Scope" disclosed herein is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0045] In this application, if there is no special description, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution. In this application, if there is no special description, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0046] In this application, unless otherwise specified, the terms "include" and "comprising" mentioned herein may be open-ended or closed-ended. For example, the terms "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0047] In the description herein, unless otherwise specified, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0048] In the prior art, the wet coating method for preparing battery pole pieces includes mixing the positive or negative active material, conductive agent, adhesive, and solvent into a slurry with a solid content of 40-60%, and then transferring the slurry to an aluminum foil or copper foil current collector; drying the slurry coated with the solvent on the current collector, heating and volatilizing to remove the solvent; rolling the dried current collector to obtain the pole piece of the secondary battery. However, this method is complex, expensive, risky, and environmentally unfriendly. The dry coating battery material processing is to first mix and stir the active main material and the conductive agent to obtain a premix, then add an adhesive to the premix to make the solid content of the electrode active material 80-98%, and then stir it under the conditions of revolution of 30-60 rpm and rotation of 40-100 rpm, and then perform aging treatment to obtain a dry coating material. However, the battery materials prepared by this method have uneven mixing between the active materials and the conductive agent and adhesive, and the conductive agent and adhesive are prone to agglomeration, resulting in large differences in the membrane adhesion and membrane resistance when forming the electrode, which brings serious uncontrollable safety impacts to the manufacturing of secondary batteries.
[0049] In the present application, the inventors have discovered that the (secondary or multiple) step-by-step feeding method can minimize the agglomeration of the adhesive and the conductive agent in the dry coating material, and that by means of a heated casting method (for example, using a high mixer with a heating device), the surface of the secondary battery active material fed in steps is wrapped with a dense bonding layer of adhesive and conductive agent, thereby obtaining a secondary battery electrode with excellent adhesion and membrane internal resistance through a dry coating process.
[0050] In the present application, the method for dry dispersing secondary battery active materials, adhesives and conductive agents includes: (1) blending the secondary battery active materials and the first adhesive, and performing heat casting to form a first blend; and (2) blending the first blend and the first conductive agent, and performing heat casting to form a second blend; wherein, based on the weight of the second blend, the content of the secondary battery active material is 80-99% by weight, and the content of the first adhesive is 0.5-10% by weight; wherein, based on the weight of the final product, the content of the first conductive agent is 0.5-5% by weight. In the present application, by adding the adhesive first and then the conductive agent in a step-by-step manner, the phenomenon of agglomeration between the adhesive and the conductive agent in the dry coating material can be greatly reduced. Moreover, the respective heat casting after adding the adhesive and the conductive agent can promote the adhesive and the conductive agent to densely wrap the surface of the secondary battery active material, providing excellent electrode adhesion and membrane internal resistance.
[0051] In one embodiment of the present application, the secondary battery active material includes a secondary battery positive electrode active material or a secondary battery negative electrode active material, which can be used to prepare a positive electrode sheet or a negative electrode sheet, respectively. Generally, the content of the secondary battery active material can be within a numerical range consisting of any two of the following values as end values: 80% by weight, 83% by weight, 86% by weight, 89% by weight, 92% by weight, 95% by weight, 98% by weight, 99% by weight. It should be emphasized that although the above values are listed in parallel, it does not mean that the numerical range consisting of any two of the above values as end points can obtain equivalent or similar performance. This also applies to the numerical range mentioned below. Regarding the preferred embodiment of the present application, the selection is made only based on the specific discussion below and specific experimental data. In an optional embodiment of the present application, the content of the secondary battery active material is 80-99% by weight or 90-99% by weight.
[0052] In one embodiment of the present application, the content of the first adhesive can be within a numerical range formed by any two of the following values as end values: 0.5 wt%, 1 wt%, 2 wt%, 4 wt%, 6 wt%, 8 wt%, 10 wt%. In an optional embodiment of the present application, the content of the first adhesive is 0.5-10 wt% or 1-4 wt%.
[0053] In one embodiment of the present application, the content of the first conductive agent can be within a numerical range formed by any two of the following values as end values: 0.5 wt%, 0.8 wt%, 1 wt%, 1.3 wt%, 1.5 wt%, 1.8 wt%, 2 wt%. In an optional embodiment of the present application, the content of the first conductive agent is 0.5-5 wt% or 0.5-2 wt%. In this method, by making the contents of the secondary battery active material, the first adhesive and the first conductive agent within the above content range, a pole piece membrane with reduced resistance, increased adhesion and better uniformity can be better prepared.
[0054] In an embodiment of the present application, the method further includes: (3) blending the second blend and the second adhesive, and performing heat casting to form a third blend; and (4) blending the third blend and the second conductive agent, and performing heat casting to form a fourth blend, wherein, based on the weight of the fourth blend, the content of the second adhesive is 0.5-10% by weight, and the content of the second conductive agent is 0.5-5% by weight. By multiple (repeated) step-by-step feeding methods, the phenomenon of agglomeration between the adhesive and the conductive agent in the dry coating material can be minimized. In addition, the respective heating casting after multiple additions of the adhesive and the conductive agent can better promote the adhesive and the conductive agent to densely wrap the surface of the secondary battery active material, providing better electrode adhesion and membrane internal resistance.
[0055] In an embodiment of the present application, the first adhesive and the second adhesive may be the same or different, including but not limited to PVA, PVDF, PTFE, CMC, SBR, fluorinated rubber, polyurethane, polyolefins. In an embodiment of the present application, the first conductive agent and the second conductive agent may be the same or different, including but not limited to carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene.
[0056] In one embodiment of the present application, the content of the second adhesive can be within a numerical range formed by any two of the following values as end values: 0.5 wt %, 1 wt %, 2 wt %, 4 wt %, 6 wt %, 8 wt %, 10 wt %. In an optional embodiment of the present application, the content of the second adhesive is 0.5-10 wt % or 1-4 wt %.
[0057] In one embodiment of the present application, the content of the second conductive agent can be within a numerical range formed by any two of the following values as end values: 0.5 wt%, 0.8 wt%, 1 wt%, 1.3 wt%, 1.5 wt%, 1.8 wt%, 2 wt%. In an optional embodiment of the present application, the content of the second conductive agent is 0.5-5 wt% or 0.5-2 wt%.
[0058] In one embodiment of the present application, the number of times steps (3) and (4) are repeated can be within a numerical range formed by any two of the following values as end values: 1 time, 2 times, 3 times, 4 times, 5 times, 6 times. Based on cost efficiency, it is preferred to repeat steps (3) and (4) once each.
[0059] In one embodiment of the present application, the rotation speed of the high mixer can be within a numerical range consisting of any two of the following values as end values: 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1900 rpm, 2000 rpm. In an embodiment of the present application, the blending is performed at a rotation speed of 1500-2000 rpm in the high mixer. In one embodiment of the present application, the heating temperature of the heating casting in the high mixer and the mold temperature unit is within the numerical range formed by any two of the following values as end values: 150°C, 170°C, 190°C, 210°C, 230°C, 250°C; and the rotation speed of the high mixer can be within the numerical range formed by any two of the following values as end values: 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1900 rpm, 2000 rpm. In an embodiment of the present application, the heating casting is carried out at a heating temperature of 150-250°C in the high mixer and the mold temperature unit. In this method, by mixing and heating casting in a high mixer and a mold temperature unit, not only can the agglomeration phenomenon between the adhesive and the conductive agent of the dry coating material be minimized, but also the surface of the secondary battery active material can be coated with a dense adhesive and conductive agent bonding layer, so that a secondary battery electrode with excellent adhesion and membrane internal resistance can be obtained through a dry coating process.
[0060] In the following, the performance improvement brought about by the dry dispersion method of the present application is characterized mainly based on secondary batteries, especially lithium-ion secondary batteries, but it should be emphasized here that the dry dispersion method of the present application can be used for any electrical device including a carbon-based electrode, and the electrical device can benefit from it.
[0061] In the specific implementation of this application, Figure 1 As shown, the method of dry dispersing secondary battery active materials, adhesives and conductive agents includes:
[0062] (A) adding X% of lithium battery positive or negative electrode active material and A1% of binder into a high-speed mixer, and dispersing them by high-speed stirring in the high-speed mixer to obtain a semi-finished product 1, wherein the speed of the high-speed mixer is 1500-2000 revolutions per minute (rpm);
[0063] (B) heating and casting the semi-finished product 1 under high mixing and stirring conditions of a high mixer and a mold temperature unit to obtain a semi-finished product 2, wherein the heating temperature is 150-250° C. and the speed of the high mixer is 1500-2000 rpm;
[0064] (C) adding B1% of the conductive agent into a high-speed mixer and mixing it again with the semi-finished product 2 at a high speed to obtain a semi-finished product 3, wherein the speed of the high-speed mixer is 1500-2000 rpm;
[0065] (D) heating and casting the semi-finished product 3 under the high mixing and stirring conditions of the high mixer and the mold temperature unit to obtain the semi-finished product 4 or the final product; wherein the heating temperature is 150-250° C. and the high mixer speed is 1500-2000 rpm;
[0066] (E) adding A2% of the adhesive into the high-speed mixer and mixing it with the semi-finished product 4 again at high speed to obtain the semi-finished product 5; wherein the speed of the high-speed mixer is 1500-2000 rpm;
[0067] (F) Under the high mixing and stirring conditions of the high mixer and the mold temperature unit, the semi-finished product 5 is heated and cast to obtain the semi-finished product 6; wherein the heating temperature is 150-250° C. and the high mixer speed is 1500-2000 rpm;
[0068] (G) adding B2% of the conductive agent into a high-speed mixer and mixing it again with the semi-finished product 6 at a high speed; wherein the speed of the high-speed mixer is 1500-2000 rpm; and
[0069] (H) Obtaining the final product.
[0070] In the embodiment of the present application, X% ranges from 80% to 99%, preferably from 90% to 99%. The positive active materials of lithium batteries include lithium cobalt oxide, ternary materials, lithium manganese oxide, lithium iron phosphate, etc.; the negative active materials of lithium batteries include carbon negative electrode materials, silicon negative electrode materials, etc.
[0071] In the embodiment of the present application, the range of B1% and B2% is 0.5%-5%, preferably 0.5%-2%. The conductive agent includes carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene and the like.
[0072] In the embodiment of the present application, the range of A1% and A2% is 0.5%-10%, preferably 1%-4%. The adhesive includes polyvinyl alcohol (PVA), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), fluorinated rubber, polyurethane, polyolefins, etc.
[0073] In this application, the high-speed mixer and the mold temperature unit are as follows: Figure 3 As shown. Among them, a represents a pot cover, b represents a pot body, c represents a cylinder, d represents a motor, e represents a large base, f represents a mixer base, and g represents a discharge port.
[0074] Secondary battery
[0075] In one embodiment of the present application, a secondary battery is provided, which can be a lithium ion secondary battery, a potassium ion secondary battery, a sodium ion secondary battery, a lithium sulfur battery, etc., and is particularly preferably a lithium ion secondary battery. The secondary battery of the present application includes a positive electrode (pole sheet), a negative electrode (pole sheet), a separator, an electrolyte / liquid, etc. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0076] [Positive electrode]
[0077] In the secondary battery of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer (or positive electrode active material layer) disposed on at least one surface of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in the thickness direction of itself, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector. In the secondary battery of the present application, the positive electrode current collector may be a metal foil or a composite current collector, for example, the metal foil may be an aluminum foil, and the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene PP, polyethylene terephthalate PET, polybutylene terephthalate PBT, polystyrene PS, polyethylene PE and its copolymers, etc.).
[0078] In the present application, the compaction density of the positive electrode active material layer of the secondary battery is controlled to reduce the ion transmission path to improve the cycle life of the secondary battery, while at the same time, the particles of the active material will not be broken due to the high compaction density, resulting in an increase in the specific surface area (BET), leading to the side reaction of the outlet line and deteriorating the cycle life of the secondary battery to a certain extent. Usually, the compaction density of the positive electrode active material layer can be 2.0-3.6g / cm 3 In one embodiment of the present application, the compaction density of the positive electrode active material layer may be within a numerical range consisting of any two of the following numerical values as end values: 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5.
[0079] In the secondary battery of the present application, the positive electrode active material (substance) may adopt the positive electrode active material for secondary batteries known in the art. For example, the positive electrode active material may include one or more of the following: lithium-containing phosphates of olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for secondary batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811)), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, one or more of lithium iron phosphate (such as LiFePO4 (LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0080] In some embodiments, the positive electrode film layer further includes a binder. Non-limiting examples of binders that can be used for the positive electrode film layer may include one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0081] In some embodiments, the positive electrode film layer further comprises a conductive agent. Examples of the conductive agent used in the positive electrode film layer may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0082] In one embodiment of the present application, the positive electrode can be prepared in the following manner: the above-mentioned components for preparing the positive electrode, such as the positive electrode active material, the conductive agent, the binder and any other components are dry dispersed, and then coated on the positive electrode collector by a dry coating process, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0083] [Negative electrode]
[0084] The secondary battery of the present application includes a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer (or called a negative electrode active material layer) arranged on at least one surface of the negative electrode current collector.
[0085] In the embodiment of the present application, the compaction density of the negative electrode active material layer may be 0.5-2.0 g / cm 3 In one embodiment of the present application, the compaction density of the negative electrode active material layer may be within a numerical range consisting of any two of the following numerical values as end values: 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0.
[0086] In one embodiment of the present application, the negative electrode film layer may include a certain amount of other commonly used negative electrode active materials in addition to the negative electrode active materials described above, for example, one or more of natural graphite, other artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from one or more of elemental silicon, silicon oxide, and silicon-carbon composites. The tin-based material may be selected from one or more of elemental tin, tin oxide compounds, and tin alloys.
[0087] In the secondary battery of the present application, the negative electrode film comprises a negative electrode active material and a binder, a conductive agent and other optional auxiliary agents. In one embodiment of the present application, the negative electrode can be prepared by the following method: the above components for preparing the negative electrode, such as the negative electrode active material, the conductive agent, the adhesive and any other components are dispersed by dry method, and then coated on the negative electrode current collector by dry coating process, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0088] As an example, the conductive agent may include one or more of superconducting carbon, carbon black (eg, acetylene black, Ketjen black), carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0089] As an example, the adhesive may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). As an example, the adhesive may include one or more of styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). Other optional additives are, for example, thickeners (such as sodium carboxymethyl cellulose CMC-Na), PTC thermistor materials, etc.
[0090] In addition, in the secondary battery of the present application, the negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate of the present application may also include a conductive primer layer (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode current collector and the first negative electrode film layer and disposed on the surface of the negative electrode current collector. In some other embodiments, the negative electrode plate of the present application may also include a covering protective layer covering the surface of the second negative electrode film layer.
[0091] In the secondary battery of the present application, the negative electrode current collector may be a metal foil or a composite current collector, for example, the metal foil may be a copper foil, a silver foil, an iron foil, or a foil composed of an alloy of the above metals. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer, and may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material base layer (such as a base layer made of materials such as polypropylene PP, polyethylene terephthalate PET, polybutylene terephthalate PBT, polystyrene PS, polyethylene PE and copolymers thereof).
[0092] [Electrolytes]
[0093] The electrolyte plays the role of conducting ions between the positive electrode plate and the negative electrode plate. The electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte). In some embodiments, the electrolyte uses an electrolyte. The electrolyte includes an electrolyte salt and a solvent. In some embodiments, the electrolyte salt can be selected from LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bisfluorosulfonyl imide), LiTFSI (lithium bistrifluoromethanesulfonyl imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluoro oxalate borate), LiBOB (lithium dioxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluoro dioxalate phosphate) and LiTFOP (lithium tetrafluoro oxalate phosphate) One or more. In one embodiment of the present application, the solvent may be selected from one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE). In one embodiment of the present application, based on the total weight of the electrolyte, the content of the solvent is 60-99% by weight, such as 65-95% by weight, or 70-90% by weight, or 75-89% by weight, or 80-85% by weight. In one embodiment of the present application, based on the total weight of the electrolyte, the content of the electrolyte is 1-40% by weight, such as 5-35% by weight, or 10-30% by weight, or 11-25% by weight, or 15-20% by weight.
[0094] In one embodiment of the present application, the electrolyte may optionally contain additives. For example, the additives may include one or more of the following: negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.
[0095] [Isolation film]
[0096] In one embodiment of the present application, the secondary battery further comprises a separator, which separates the anode side of the secondary battery from the cathode side, and provides selective permeation or blocking for substances of different types, sizes and charges in the system. For example, the separator can insulate electrons, physically isolate the positive and negative active substances of the secondary battery, prevent internal short circuits and form an electric field in a certain direction, and allow the ions in the battery to pass through the separator and move between the positive and negative electrodes. In one embodiment of the present application, the material used to prepare the separator may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different. In an embodiment of the present application, the separator is selected from polyolefin separators, polyester separators, polyimide separators, polyamide separators and cellulose separators.
[0097] In one embodiment of the present application, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly / bare cell by a winding process or a lamination process.
[0098] In one embodiment of the present application, the secondary battery may include an outer package, which can be used to encapsulate the above-mentioned electrode assembly and electrolyte. In some embodiments, the outer package of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. In other embodiments, the outer package of the secondary battery can be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0099] The shape of the secondary battery of the present application can be cylindrical, square or any other shape. Figure 4 The secondary battery 5 is a square structure as an example. Figure 5 Shows Figure 4 The exploded view of the secondary battery 5 is shown in FIG. 5 . The outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate. The bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity. The cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly is encapsulated in the receiving cavity, and the electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more.
[0100] In one embodiment of the present application, a plurality of secondary batteries may be assembled together to form a battery module, wherein the battery module includes two or more secondary batteries, and the specific number depends on the application of the battery module and the parameters of a single battery module.
[0101] Figure 6 4 is an example of a battery module. Figure 6 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0102] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0103] In one embodiment of the present application, two or more of the above-mentioned battery modules can be assembled into a battery pack, and the number of battery modules contained in the battery pack depends on the application of the battery pack and the parameters of the individual battery modules. The battery pack may include a battery box and a plurality of battery modules disposed in the battery box, and the battery box includes an upper box body and a lower box body, and the upper box body can cover the lower box body and match well with it to form a closed space for accommodating the battery modules. Two or more battery modules can be arranged in the battery box in a desired manner.
[0104] Figure 7 and Figure 8 1 is a battery pack 1 as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0105] Electrical devices
[0106] In one embodiment of the present application, the electric device of the present application includes at least one of the secondary battery, battery module, or battery pack of the present application, and the secondary battery, battery module, or battery pack can be used as a power source of the electric device, and can also be used as an energy storage unit of the electric device. The electric device includes but is not limited to mobile digital devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0107] Fig. 9 The device is used as an example. The device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the device's requirements for high power and high energy density, a battery pack or a battery module can be used.
[0108] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0109] In the following, the influence of the secondary battery manufactured according to the embodiment of the present application on the performance of the electrochemical device is characterized based on specific examples, but it should be pointed out that the protection scope of the present application is defined by the claims and is not limited to the above specific embodiments.
[0110] Example
[0111] Unless otherwise stated, all raw materials used in the present invention were of analytical grade.
[0112] Example 1
[0113] like Figure 1 As shown, first, 96 wt% of lithium cobalt oxide as a positive electrode active material for lithium batteries and 1 wt% of polyvinylidene fluoride (PVDF) as a binder are added to a high-speed mixer. The high-speed mixer is stirred and dispersed at 1800 rpm. The particles in the blend have Figure 2 Then, the mold temperature unit was turned on and the heating casting was carried out at a temperature of 200°C under high mixing conditions for 3 minutes. At this time, the particles in the blend had Figure 2 SEM characterization of number ②.
[0114] Next, 1 wt% of conductive carbon black (conductive agent Super P) was added to the high-speed mixer. The mixture was stirred and dispersed at 1800 rpm. Figure 2 Then, the mold temperature unit was turned on and the heating casting was carried out at a temperature of 200°C under high mixing conditions for 3 minutes. At this time, the particles in the blend had Figure 2 SEM characterization of number ④ in the figure.
[0115] Next, 1 wt% of polyvinylidene fluoride (PVDF) as a binder is added to the high-speed mixer. The high-speed mixer is stirred and dispersed at 1800 rpm. The particles in the blend have Figure 2 Then, the mold temperature unit was turned on and the heating casting was carried out at a temperature of 200°C under high mixing conditions for 3 minutes. At this time, the particles in the blend had Figure 2 SEM characterization of number ⑥.
[0116] Next, 1 wt% of conductive carbon black (conductive agent Super P) was added to the high-speed mixer. The mixture was stirred and dispersed at 1800 rpm. Figure 2 SEM characterization of number ⑦.
[0117] from Figure 2 From the SEM characterizations, it can be seen that the surface of the lithium battery active material particles can be evenly coated with adhesive and conductive agent particles through the step-by-step feeding and heating casting process, thereby reducing the resistance of the electrode film prepared subsequently, increasing the adhesion and improving the uniformity.
[0118] Example 2
[0119] First, 94 wt% of nickel-cobalt-manganese oxide as a positive electrode active material for lithium batteries and 4 wt% of polyvinylidene fluoride (PVDF) as a binder were added to a high-speed mixer. The mixture was stirred and dispersed at 2000 rpm in the high-speed mixer. Then, the mold temperature unit was turned on and heated and cast at 220°C under high-speed mixing conditions.
[0120] Next, 2 wt% of conductive carbon black (conductive agent Super P) as a conductive agent was also added to the high-speed mixer. The mixture was stirred and dispersed at a high speed of 2000 rpm in the high-speed mixer. Then, the mold temperature unit was turned on, and the heat casting was performed at a temperature of 220°C under high mixing conditions to obtain a positive electrode active coating material with a surface uniformly coated with adhesive and conductive agent particles. Through SEM testing, it was observed that the surface of the material particles was uniformly coated with a layer of PVDF and SP particles.
[0121] Example 3
[0122] First, 96 wt% of nickel-cobalt-manganese oxide as a positive electrode active material for lithium batteries and 2 wt% of polyvinylidene fluoride (PVDF) as a binder were added to a high-speed mixer. The high-speed mixer was stirred and dispersed at 2000 rpm. Then, the mold temperature unit was turned on and heated and cast at a temperature of 220°C under high-speed mixing and stirring conditions.
[0123] Next, 2 wt% of conductive carbon black (conductive agent Super P) as a conductive agent is also added to the high-speed mixer. The high-speed mixer is stirred and dispersed at 2000 rpm. Then, the mold temperature unit is turned on, and the heat casting is performed at a temperature of 220°C under high-mix stirring conditions, thereby obtaining a positive electrode active coating material with a surface uniformly coated with binder and conductive agent particles.
[0124] Example 4
[0125] First, 95 wt% of nickel-cobalt-manganese oxide as a positive electrode active material for lithium batteries and 3 wt% of polyvinylidene fluoride (PVDF) as a binder were added to a high-speed mixer. The mixture was stirred and dispersed at 2000 rpm in the high-speed mixer. Then, the mold temperature unit was turned on and heated and cast at a temperature of 220°C under high-speed mixing conditions.
[0126] Next, 1 wt% of conductive carbon black (conductive agent Super P) and 1 wt% of carbon nanotubes (CNT) as a conductive agent are also added to the high mixer. High-speed stirring and dispersion are performed in the high mixer at 2000 rpm. Then, the mold temperature unit is turned on, and heating casting is performed at a temperature of 220°C under high mixing and stirring conditions, thereby obtaining a positive electrode active coating material with a surface uniformly coated with adhesive and conductive agent particles. Through SEM testing, it was observed that carbon nanotubes (CNT) are difficult to disperse.
[0127] Example 5
[0128] First, 94 wt% of lithium iron phosphate as a positive electrode active material for lithium batteries and 4 wt% of polyvinylidene fluoride (PVDF) as a binder were added to a high-speed mixer. The high-speed mixer was stirred and dispersed at 2000 rpm. Then, the mold temperature unit was turned on and heated and cast at a temperature of 220°C under high-speed mixing conditions.
[0129] Next, 2 wt% of conductive carbon black (conductive agent Super P) as a conductive agent was also added to the high-speed mixer. The mixture was stirred and dispersed at a high speed of 2000 rpm in the high-speed mixer. Then, the mold temperature unit was turned on, and the heat casting was performed at a temperature of 220°C under high mixing conditions, thereby obtaining a positive electrode active coating material with a surface uniformly coated with adhesive and conductive agent particles. SEM testing showed that the coating was good.
[0130] Example 6
[0131] First, 96% by weight of lithium iron phosphate as a positive electrode active material for lithium batteries and 2% by weight of polyvinylidene fluoride (PVDF) as a binder were added to a high-speed mixer. The high-speed mixer was stirred and dispersed at 2000 rpm. Then, the mold temperature unit was turned on and heated and cast at a temperature of 220°C under high-speed mixing conditions.
[0132] Next, 2 wt% of conductive carbon black (conductive agent Super P) as a conductive agent was also added to the high-speed mixer. The mixture was stirred and dispersed at a high speed of 2000 rpm in the high-speed mixer. Then, the mold temperature unit was turned on, and the heat casting was performed at a temperature of 220°C under high mixing conditions, thereby obtaining a positive electrode active coating material with a surface uniformly coated with adhesive and conductive agent particles. SEM testing showed that the coating was good.
[0133] Comparative Example 1
[0134] First, 94 wt% of nickel cobalt manganese oxide as a positive electrode active material for lithium batteries and 4 wt% of polyvinylidene fluoride (PVDF) as a binder were added to a high mixer. At 2000 rpm, high-speed stirring and dispersion were performed in the high mixer. Next, 2 wt% of conductive carbon black (conductive agent Super P) as a conductive agent was also added to the high mixer. At 2000 rpm, high-speed stirring and dispersion were performed in the high mixer to obtain a positive electrode active coating material. SEM measurements showed that PVDF and SP had serious agglomeration.
[0135] Comparative Example 2
[0136] First, 94 wt% of nickel cobalt manganese oxide as a positive electrode active material for lithium batteries and 4 wt% of polyvinylidene fluoride (PVDF) as a binder were added to a high mixer. At 2000 rpm, high-speed stirring and dispersion were performed in the high mixer. Next, 2 wt% of conductive carbon black (conductive agent Super P) as a conductive agent was also added to the high mixer and heated. At 2000 rpm, high-speed stirring and dispersion were performed in the high mixer to obtain a positive electrode active coating material. SEM measurements showed that PVDF and SP had serious agglomeration.
[0137] Comparative Example 3
[0138] First, 95 wt % of nickel cobalt manganese oxide as a positive electrode active material for lithium batteries and 4 wt % of polyvinylidene fluoride (PVDF) as a binder were added to a high mixer. At 2000 rpm, high-speed stirring and dispersion were performed in the high mixer. Next, 1 wt % of conductive carbon black (conductive agent Super P) as a conductive agent was also added to the high mixer. At 2000 rpm, high-speed stirring and dispersion were performed in the high mixer to obtain a positive electrode active coating material. SEM measurement showed that PVDF and SP had serious agglomeration.
[0139] Comparative Example 4
[0140] First, 94 wt% of nickel-cobalt-manganese oxide as a positive electrode active material for lithium batteries and 4 wt% of polyvinylidene fluoride (PVDF) as a binder were added to a high-speed mixer. The high-speed mixer was stirred and dispersed at 2000 rpm. Then, the high-temperature mixing was performed again at 280°C by an oil temperature machine.
[0141] Next, 2 wt % of KS-6 as a conductive agent was added to the high-speed mixer and stirred and dispersed at 2000 rpm in the high-speed mixer to prepare a positive electrode active coating material.
[0142] Test Case
[0143] The positive electrode active coating materials prepared in Example 2 and Comparative Examples 1-2 were dry-applied to the positive electrode current collector with a coating thickness of 120 micrometers (μ), and after drying and cold pressing under a pressure of 40 N, a positive electrode sheet was formed. The adhesion, cohesion and sheet resistance of the sheet were tested according to the following methods.
[0144] Adhesion Test Method
[0145] Cut a 2cm×10cm rectangle of the positive electrode sheet (coated with positive active material layer on both sides) for sample testing. Take a 5cm tape and stick the sample on the iron sheet used for testing, where the upper end of the sample is pasted flush with the iron sheet, leaving a blank sheet of about 5cm in length at the lower end. Clamp the lower end of the iron sheet to the lower chuck of the tensile machine, and clamp the lower end of the blank sheet to the upper chuck of the tensile machine in reverse. Start the tensile machine startup program, and the test result is the bonding force.
[0146] Cohesion Test Method
[0147] Cut a 2cm×10cm rectangle from the positive electrode sheet (coated with positive active material layer on both sides) for sample testing. Use a 5cm tape to stick the test sample on the iron sheet used for testing, where the upper end of the sample is pasted flush with the iron sheet. Use a 12cm long cohesive tape to stick on the other side of the electrode sheet, where the upper end is pasted flush with the iron sheet. The lower end of the iron sheet is clamped in the lower chuck of the tensile testing machine, and the excess cohesive tape is clamped in the reverse direction on the upper chuck of the tensile testing machine. Turn on the tensile testing machine startup program, and the test result is the cohesive force.
[0148] Diaphragm resistance test method
[0149] The resistance per unit area of the positive electrode plate can be tested by a test method known in the art. As an example, the following method can be used: the test instrument is the IEST BER1000 plate resistor meter of Yuanneng Technology. The specific steps include: cutting a square test sample of 10cm×10cm from the positive electrode plate (double-sided coating of the positive electrode active material layer), clamping the upper and lower sides of the test sample between the two conductive terminals of the internal resistance tester, and applying a certain pressure to fix it, and testing the resistance R of the test sample. Among them, the diameter of the conductive terminal is 14mm, the applied pressure is 15MPa~27MPa, and the sampling time ranges from 5s to 17s. The resistance per unit area of the positive electrode plate is calculated according to the formula r=R / S, where S is the contact area between the conductive terminal and the test sample (usually it can be considered as the cross-sectional area of the conductive terminal); R is the resistance value of the sample read by the detection instrument.
[0150] Table 1:
[0151]
[0152]
[0153] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for dry dispersing a secondary battery active material, a binder and a conductive agent, the method comprising: (1) blending the secondary battery active material and the first binder, and performing heat casting under blending conditions to form a first blend; and (2) mixing the first blend and the first conductive agent, and performing heat casting under the mixing condition to form a second blend; Wherein, based on the weight of the second blend, the content of the secondary battery active material is 80-99 weight %, and the content of the first binder is 0.5-10 weight %; and based on the weight of the final product, the content of the first conductive agent is 0.5-5 weight %.
2. The method according to claim 1, characterized in that The method further comprises: (3) blending the second blend and a second binder, and performing heat casting under blending conditions to form a third blend; and (4) blending the third blend and the second conductive agent, and performing heat casting under the blending condition to form a fourth blend, wherein the content of the second adhesive is 0.5-10 wt % and the content of the second conductive agent is 0.5-5 wt % based on the weight of the fourth blend.
3. The method according to claim 2, characterized in that The method further comprises: repeating steps (3) and (4) at least once.
4. The method according to any one of claims 1 to 3, characterized in that: The content of the secondary battery active material is 90-99% by weight, the content of the first binder is 1-4% by weight; and the content of the first conductive agent is 0.5-2% by weight.
5. The method according to any one of claims 2-3, characterized in that: The first adhesive and the second adhesive are the same or different, wherein the content of the second adhesive is 1-4 weight %; and The first conductive agent and the second conductive agent are the same or different, and the content of the second conductive agent is 0.5-2 weight %.
6. The method according to any one of claims 1 to 3, characterized in that: The blending is carried out in a high-speed mixer at a rotation speed of 1500-2000 rpm; and The heating casting is carried out in a high-speed mixer and a mold temperature unit at a heating temperature of 150-250°C.
7. A method for preparing a secondary battery pole piece by dry coating, the method comprising: The second blend or the fourth blend prepared by the method according to any one of claims 1 to 6 is applied onto a current collector by dry coating.
8. A secondary battery, characterized in that: The secondary battery comprises a pole piece prepared by the method according to claim 7.
9. A battery module, characterized in that: Comprising the secondary battery according to claim 8.
10. A battery pack, characterized in that: The invention comprises the secondary battery according to claim 8 or the battery module according to claim 9.
11. An electrical device, characterized in that: It comprises the secondary battery according to any one of claims 8, the battery module according to claim 9, or the battery pack according to claim 10, wherein the secondary battery, the battery module or the battery pack is used as a power source for the electrical device or an energy storage unit for the electrical device.
Citation Information
Patent Citations
Preparation method of anode slurry of lithium ion battery
CN102683644A
Sodium ion battery and sodium ion electrode preparation process
CN112103412A